A study on decision making opportunity between genders in public sector / Mohd Hafiz Halun and Rannol Jaimin - Halun, Mohd Hafiz; Jaimin, Rannol (2013)
The purpose of this study is to study on decision making opportunity between genders in public sector. Therefore, the findings can be used as a reference for academic purposes. Descriptive study is undertaken in this research which data collected from primary and secondary data. It took 4 months to conduct this research until the result from the survey has been gathered. 150 questionnaires were distributed and were later analyzed. This project paper consists of five chapters. Chapter one gives the reader an overview of background of study, problem statement, and research objectives. The literature review can be found in chapter 2. Chapter three tells us the research design and methodology. It goes on to explain the data collection method that will be used and how the data will be analyzed. Chapter four will reveal the finding of the survey and next chapter will provide the conclusion and recommendation of the survey. From the finding, it is correlated with the literature review which has the significant role in help us to reach our objectives. Thus, it will enable us to exercise and acquire effective interpersonal and communication skills in organizations. Lastly, it also enables us to put into practice our academic knowledge and skills acquired at University of MARA Technology (UiTM).